MiR-29b Downregulation Induces Phenotypic Modulation of Vascular Smooth Muscle Cells: Implication for Intracranial Aneurysm Formation and Progression to Rupture - Sun, Liqian; Zhao, Manman; Zhang, Jingbo; Lv, Ming; Li, Youxiang; Yang, Xinjian; Liu, Aihua; Wu, Zhongxue (Cellular physiology and biochemistry, 2017)
Background/Aims: Our previous microarray results identified numerous microRNAs (miRNAs), including miR-29b, that were differentially expressed in the serum of intracranial aneurysm (IA) patients. The current study aimed to investigate whether miR-29b downregulation in IA could promote the phenotypic modulation of vascular smooth muscle cells (VSMCs) involved in the pathogenesis of aneurysm by activating ATG14-mediated autophagy. Methods: First, the levels of miR-29b and autophagy related genes (ATGs) between IA patients and normal subjects were compared. Next, we modified the level of miR-29b via lentivirus particles in the VSMCs and examined the effects of miR-29b on proliferation, migration, and phenotypic modulation of VSMCs from a contractile phenotype to a synthetic phenotype, as well as the levels of autophagy. Finally, the binding of miR-29b to the 3’UTR of ATG14 mRNA and its effects on ATG14 expression were analysed by a luciferase reporter assay and Western blot, respectively. Results: The level of miR-29b was decreased, and autophagy markers were increased in the IA patients compared to that of the normal subjects. Knockdown of miR-29b significantly promoted VSMCs proliferation and migration and, more importantly, induced the phenotypic modulation associated with autophagy activation, whereas miR-29b overexpression showed the opposite effects. The luciferase reporter assay demonstrated that ATG14 was a functional target gene of miR-29b. Notably, knockdown of ATG14 by siRNA apparently abrogated miR-29b inhibition-mediated phenotypic modulation. Conclusion: Downregulation of miR-29b induced VSMCs phenotypic modulation by directly activating ATG14-mediated autophagy, which is associated with the formation, growth and rupture of IAs.